Development of quasi-flexible solid polymer blend electrolytes and boron carbide reinforced tea waste electrodes for supercapacitors - Azemtsop Manfo, Theodore; Şahin, Mustafa Ergin; Bal Altuntaş, Derya (Elsevier, 2025)
This study aims to create a prototype supercapacitor (SC) using free-standing-solid polymer electrolytes and tea waste (TW) doped boron carbide (B4C) electrodes. Quasi-solid polymer electrolyte (QSPE) films are made using a solution-casting approach, with poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) and polymethyl methacrylate (PMMA) as host polymers and potassium oxide (KOH) salt as an ion source. PVDF-HFP: PMMA (80:20 wt%) + 30 wt% KOH showed a maximal ion conductivity of 3.63 ± 0.18 × 10− 4 S cm− 1 and a relative permittivity of 31.48 × 103 at 105 Hz at ambient temperature. The linear speed voltammetry (LSV) test measurements demonstrate that the enhanced solid polymer electrolyte (SPE) sample can endure breakdown up to 1.85 V. The study utilized TW: B4C (95:05 wt%) activated electrode material for an SC device embedded with the highly conductive blend electrolyte film. The galvanostatic charge/discharge (GCD) method revealed the charge/ discharge behavior of an ideal SC indicating a low Faradic process and equivalent series resistance (ESR) value for the capacitor with a coulombic efficiency (η) of 100 %. The GCD data reveals that the SC’s specific capacitance (Csp) was 42.30 F g− 1 , and the calculated value of energy density (Es) and power density (Pd) was 21.15 Wh. g− 1 and 69.21 × 103 Wg− 1 at 5 mA g− 1 respectively. Cyclic voltammetry (CV) aids in studying the capacity behavior of the electrical double-layer capacitor (EDLC), revealing no redox peaks over a potential range of − 1 to +1V and Csp was 50.72 F g− 1 . The Csp of 56.67 F g− 1 was obtained using the Impedance data recorded over a range of frequency 0.01–1 MHz.
Keywords: Polymer blend electrolyte; Electrode; Capacitance; Ionic conductivity; Supercapacitor; electrodes; supercapacitors; electrochemistry; fi=Sähkötekniikka|en=Electrical Engineering|